Monitoring neonatal brain function: recent advances in functional near-infrared spectroscopy (fNIRS) - Xu, Fei; Li, Jie; Zheng, Chao; Mi, Lanlan (Frontiers in Pediatrics, 2026)
Understanding functional brain development in neonates represents a critical frontier in neuroscience. Due to the high plasticity of the infant brain, early detection of functional abnormalities and timely interventions are essential to improving long-term neurodevelopmental outcomes. However, progress in this field has been limited by the constraints of conventional neuroimaging modalities. The emergence of functional near-infrared spectroscopy (fNIRS) has opened new avenues for neonatal brain research. This narrative review provides a comprehensive synthesis of recent advancements in fNIRS for neonatal brain monitoring. We aim to delineate the technical principles of fNIRS, critically evaluate its applications in developmental assessment and clinical care, and discuss its future translational potential. By consolidating this evidence, this review clarifies the unique value of fNIRS, addresses the need for a consolidated framework in this rapidly evolving field, and identifies key challenges to guide future research. As a non-invasive, portable, and motion-resilient optical imaging technique, fNIRS is particularly well-suited for bedside assessment and naturalistic observation of brain function. Relying on the principle of neurovascular coupling, fNIRS measures changes in cerebral oxygenation to detect neural activity, thereby providing novel insights into cognitive development, pathological processes, and therapeutic responses in neonates. With continuous advancements in technology and methodology, fNIRS applications in neonatology have expanded markedly, facilitating significant progress in areas such as sensory processing and clinical evaluation of brain injuries. This review provides a comprehensive analysis of recent developments in fNIRS for neonatal brain monitoring. It outlines the technique's foundational principles, technical characteristics, advantages and limitations, and explores its applications in developmental assessment, clinical surveillance, and disease diagnostics, while offering perspectives on its clinical utility and future directions.